Changes in flight paths of large-bodied birds after construction of large terrestrial wind turbines. (15th July 2021) - Therkildsen, Ole R.; Balsby, Thorsten J.S.; Kjeldsen, Jørgen P.; Nielsen, Rasmus Due; Bladt, Jesper; Fox, Anthony D.
Abstract: The proliferation of ever-larger wind turbines poses risks to wildlife, especially from avian collision, yet avoidance behaviour of large-bodied, long-lived bird species in relation to wind turbines remains little studied away from collision "black spots" and offshore marine environments. Here, three-dimensional flight trajectory data are reported from a laser range-finder study of local movements of large-bodied birds (e.g. swans, geese, gulls, cormorants, raptors and cranes, whose populations are relatively more demographically sensitive to collision mortality) in relation to seven terrestrial 150-222 m high (mean 182 m) wind turbines constructed in Denmark in a N-S line. Comparisons of two-dimensional flight passages between turbines pre- (n = 287) and post-construction (n = 1210) showed significant (P < 0.0001) reductions from 48% to 35% within 150 m of each turbine, with corresponding increase 200-300 m from turbines. Results also showed a significant (P < 0.001) 50% reduction in the percentage of avian passages (from 21% to 10%) through the maximum turbine sweep area after construction and that the proportion of birds that passed between turbines at heights below (0-45 m) and above the turbine sweep area (> 182 m) were significantly greater (P < 0.0001) post-construction than prior to construction. These are the first results from tracking large-bodied bird flight trajectories to show the magnitude of their vertical and horizontal adjustments to the presence of turbines, which have implications for assumptions of even flight densities made by collision risk models currently used to predict avian turbine collision rates. Highlights: Larger wind turbines (>155 m high) increase collision risks to large bodied birds. We used range-finders to construct 3D bird trajectories at a turbine test centre. Pre-/post-construction comparisons confirmed fewer flights within 150 m of turbines. Relative proportions of flights in the rotor sweep zones halved post-construction. Such flight modifications have implications for current collision risk models.